1997
DOI: 10.1007/s002280050341
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced attack of bronchial asthma in inpatients: a 20-year survey of the Comprehensive Hospital Drug Monitoring Programme on adverse drug reactions, Berne/St. Gallen

Abstract: Epidemiological aspects of attacks of bronchial asthma related to drugs are prospectively studied in inpatients of three teaching hospitals in the Comprehensive Hospital Drug Monitoring (CHDM)-programme. Results are based on 34,840 individual patients (among 48,005 consecutive admissions) in the years 1974-1993. Between 1974 and 1993, every patient admitted to any of the three medical clinics in the CHDM programme was monitored for any suspicion of an adverse drug reaction (ADR); every drug exposure period dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Aspirin-induced asthma has been shown to have a prevalence of 0.3% in the normal population [18]and approximately 10% in asthmatic subjects [19]. Hoigné et al [20]reported from the Comprehensive Hospital Drug Monitoring Program (CHDM) with 34,849 hospital admissions over 20 years that asthma induced by NSAIDs was found in 0.014% of the monitored patients, asthma induced by aspirin in 0.018% and induced by paracetamol in 0.008%. In the 3 lethal cases metamizol was injected intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin-induced asthma has been shown to have a prevalence of 0.3% in the normal population [18]and approximately 10% in asthmatic subjects [19]. Hoigné et al [20]reported from the Comprehensive Hospital Drug Monitoring Program (CHDM) with 34,849 hospital admissions over 20 years that asthma induced by NSAIDs was found in 0.014% of the monitored patients, asthma induced by aspirin in 0.018% and induced by paracetamol in 0.008%. In the 3 lethal cases metamizol was injected intravenously.…”
Section: Discussionmentioning
confidence: 99%